IMPACT OF EXECUTION OF CREATIVE TASK ON EVOKED BRAIN ACTIVITY (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
n the article changes in evoked potentials (EP) resulting from the execution of creative verbal tasks have been studied. Analysis of amplitude characteristics of evoked potentials caused by light stimuli revealed a significant increase in the amplitude of N200 component in frontal and prefrontal areas of the left hemisphere. An increase in the amplitude of N200 component in the temporo-parieto-occipital areas of the right hemisphere was also revealed. The obtained data lead us to the assumption that implementation of creative tasks with expressed elements of complexity is accompanied with significant activity of the frontal and temporoparieto- occipital areas of the cerebral cortex.
Keywords: frontal cortex, posterior associative area, evoked potentials, creative process